(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The present study aimed to develop lipid-coated gabapentin-loaded graphene oxide-mesoporous silica nanocomposites (LC-GAB-GO-MSN) as a novel drug delivery system. The objective was to address the poor permeability and low bioavailability issues associated with Gabapentin (GAB), a BCS Class III drug, by utilizing the distinctive properties of GO-MSN nanocomposites to enhance drug delivery efficiency. GAB loading within the nanocomposites was achieved through passive loading techniques, while lipid coating was carried out employing a modified thin film hydration method. Spectral characterization was conducted to determine the entrapment efficiency of GAB within the nanocomposites. Drug release studies evaluated pharmacological release kinetics developed LC-GAB-GO-MSN and GAB-GO-MSN nanocomposites. The spectral characterizations revealed an entrapment efficiency of 51.25% for GAB-MSN and 68.19% for GAB-GO-MSN. Moreover, drug release studies (in vitro) demonstrated 95.70% and 70.83% drug release from LC-GAB-GO-MSN and GAB-GO-MSN nanocomposites, respectively. The design of lipid-coated LC-GAB-GO-MSN through GO-MSN incorporation followed by lipid coating offered a controlled release profile. LC-GAB-GO-MSN nanocomposites showed promise for delivering GAB and other pharmaceutical compounds with enhanced payload capacity and release kinetics, highlighting their potential advantages over current methodologies and the important role of protocells in the development of cargo delivery systems.